A poetic interpretation of the intellect: A translation from Yusuf Nabahani’s Majmu’ Thalathah Kutub - Mohammed Muneer'deen, Olodo Al-Shafi'i (2017)
The main focus of this paper is 'the intellect' and 'the poetic interpretation' found in Nabahani's Majmu’ thalathah kutub'. In other words, this paper is an explanation of the intellection, its functions, and veracity from the view of Nabahani. The paper shows some comparison between the concept of the intellect (al-‘Aql) in Islam and other religions, precisely Christianity. While the paper has Nabahani's opinion in focus, it has not claimed to have represented everything he has said concerning the intellect and it has not limited the views expressed herein to him alone. This paper is purposely focused on presenting the poetic interpretation as projected by al-Nabahani himself; the poetic interpretational analysis and commentation are beyond this paper and would be submitted in the major study of the concept of the intellect.